دراسة الشخصيّة والتّشخيص (توصيف الشخصيّات) في روايات مابعد الاستعمارية (رواية ذاکرة الجسد: أُنموذجاً) - صالحي, پیمان (Journal of College of Education, 2020)
Choosing the right characters for the story is the most important thing the writer does, because the character is the axis and the basis of the story that all other events revolve around. Since the elements of personality and characterization have a special place in post-colonial novels, this research, using the descriptive-analytical and statistical methodologies, tried to shed light on the personality and how it is presented in the novel “Memory of the Body” by the Algerian novelist Ahlam Mostaghanemi. The results tell us that the writer during the process of dialogue, behavior, and the current of consciousness and summons of real characters in the form of artistic, political, historical, and literary prototypes, in addition to creating an appropriate relationship between characters and other anecdotal elements, used the character element in her narration in an artistic way given that the characters in This novel is one of the realistic models that participated in the Algerian revolution and the events that followed. The novelist benefited from the point of view of the central and sub-personalities to present some characters, and this method depicts the character more realistically and certainly has a greater impact. Second, sometimes she unleashes characters that make themselves more distinctive by their actions. This process plays an important role in the author's commitment to the true and original principle of the characters of the novel. In addition, at the end of the research, the present study clarifies, by presenting many diagrams, the types of personality in the novel.
Keywords: Ahlam Mostaghanemi, body memory, characterization, novel, postcolonial.